Strategi Pengembangan Sektor Kelautan untuk Pemberdayaan Ekonomi Masyarakat Pesisir: Tinjauan Literatur Sistematis - Akbar, Syahrir; Putra, Rehan Perdana; Firmansyah, Muhammad Vicky; Faizal, M Zakaria (Jurnal Manajemen Pesisir dan Laut, 2025)
Indonesia as a maritime country has great potential in the marine sector to improve the welfare of coastal communities, although it has not been optimally utilized. This study aims to formulate a strategy for developing the marine sector through a systematic literature review and SWOT analysis. The results of the study identified key strengths such as abundant marine resources, a large number of fishermen, and a strategic geographical position. Weaknesses include limited capital for business actors, limited marketing access, and minimal infrastructure and facilities. Opportunities include global demand for marine products, blue economy policies, and the development of marine-based MSMEs. The main threats are overexploitation, illegal fishing, and weather and climate fluctuations. However, the potential of the marine sector can be optimized with best practice-based strategies to encourage economic empowerment of coastal communities. Keywords: Strategy, Development, Marine, Economic Empowerment, Coastal Communities